User performance and reading strategies for metro maps: An eye tracking study. Issue 1 (2nd January 2017) - Netzel, Rudolf; Ohlhausen, Bettina; Kurzhals, Kuno; Woods, Robin; Burch, Michael; Weiskopf, Daniel
Abstract : We conducted a controlled empirical eye tracking study with 40 participants using schematic metro maps. The study focused on two aspects: determining different reading strategies and assessing user performance. We considered the following factors: color encoding (color vs. gray-scale), map complexity (three levels), and task difficulty (three levels). There was one type of task: find a route from a start to a target location and state the number of transfers that have to be performed. To identify reading strategies, we annotated fixations of scanpaths, computed a transition matrix of each annotated scanpath, and used these matrices as input to cluster scanpaths into groups of similar behavior. We show how these reading strategies relate to the geodesic structure of the scanpaths' fixations projected onto the geodesic line that connects start and target locations. The analysis of the eye tracking data is complemented by statistical inference working on two eye tracking metrics (average fixation duration and saccade length). User performance was evaluated with a statistical analysis of task correctness and completion time. Our study shows that the design factors have a significant impact on user task performance. Also, we were able to identify typical reading strategies like directly finding a path from start to target location. Often, participants check the correctness of their result multiple times by moving back and forth between start and target. Our findings also indicate that the choice of reading strategies does not depend on whether color or gray-scale encoding is used.